Analisis Implementasi Metode Perhitungan Penyusutan Aset Tetap Dan Dampaknya Terhadap Laba Pada PT Perkebunan Nusantara II Kebun Bandar Klippa - Munadya Puteri Andisty; Hendra Harmain; Nurwani Nurwani (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research aims to determine the implementation of the fixed asset depreciation method at PT Perkebunan Nusantara II Kebun Bandar Klippa and determine the implementation of fixed asset depreciation calculations in accordance with the fixed asset depreciation method based on PSAK 16 at PT Perkebunan Nusantara II Kebun Bandar Klippa and determine the impact of implementing the depreciation method fixed assets to profits at PT Perkebunan Nusantara II Kebun Bandar Klippa. This research uses a research methodology with a descriptive qualitative research approach. Data collection techniques in this research are structured interview techniques and documentation techniques. Based on the research results, it was found that the company's policy regarding the treatment of fixed asset depreciation methods is in accordance with PSAK 16. Calculation of fixed asset depreciation using the straight line method produces a relatively constant asset depreciation expense, while using the sum of the year digits and declining balance method produces a higher asset depreciation expense. at the beginning of the year and decreased in the following years. The impact of implementing the fixed asset depreciation calculation method on company profits shows that allocating depreciation costs calculated using the straight line method produces higher profits compared to using the sum of years and declining balance method.